Screening and genetic analysis of resistance to peanut stunt virus in soybean: identification of the putative Rpsv1 resistance gene - Saruta, Masayasu (Japanese Society of Breeding, 2012)
The peanut stunt virus (PSV) causes yield losses in soybean and reduced seed quality due to seed mottling. The objectives of this study were to determine the phenotypic reactions of soybean germplasms to inoculation with two PSV isolates (PSV-K, PSV-T), the inheritance of PSV resistance in soybean cultivars, and the locus of the PSV resistance gene. We investigated the PSV resistance of 132 soybean cultivars to both PSV isolates; of these, 73 cultivars exhibited resistance to both PSV isolates. Three resistant cultivars (Harosoy, Tsurunotamago 1 and Hyuga) were crossed with the susceptible cultivar Enrei. The crosses were evaluated in the F(1), F(2) and F(2:3) generations for their reactions to inoculation with the two PSV isolates. In an allelism test, we crossed Harosoy and Tsurunotamago 1 with the resistant cultivar Hyuga. The results revealed that PSV resistance in these cultivars is controlled by a single dominant gene at the same locus. We have proposed Rpsv1, as the name of the resistance gene in Hyuga. We also constructed a linkage map using recombinant inbred lines between Hyuga × Enrei using 176 SSR markers. We mapped Rpsv1 near the Satt435 locus on soybean chromosome 7.